“The Cotter’s Saturday Night” by Robert Burns in Russian Translation and Literary-Critical Reception of 19 Century - D. N. Zhatkin; N. S. Futlyaev (Научный диалог)
The article for the first time comprehensively comprehends the Russian translation and literary-critical reception of the poem “The Cotter’s Saturday Night” by Robert Burns during the 19th century. The analysis of translations and transcriptions of this piece in Russian language by I. I. Kozlov (1829), D. V. Kostomarov (1861), A. M. Fedorov (1896) is made. As a result of the analysis, the specificity of the approaches of each of the interpreters to the understanding of the Scottish poet’s conception, to the interpretation of the motives of villagers’ patriarchal life, the primordial national religiosity, faith in fate, the inevitability of the circumstances to be overcome is revealed. It is noted that none of the Russian poets-translators of the 19th century managed to preserve the formal features of the original and the characteristic tone of the narrative, permeated with a sense of belonging to the moral bonds of rural life. It is emphasized that “The Cotter’s Saturday Night” appeared outside the broad context of Burns’s works, which formed an idea of a specific, isolated place of this work in the poet’s heritage. It is indicated that at the same time the Russian translations of “The Cotter’s Saturday Night” fully reflected the ideas of poetic translation, the circumstances of social life, ideological and artistic and aesthetic views of the interpreters themselves. Russian critics’ reaction to Burns’s poem and its Russian translations contained in the articles by V. G. Belinsky, O. I. Senkovsky, N. A. Polevoy, P. I. Weinberg, etc. is also comprehended.